Comparison of Recurrence Patterns and Salvage Treatments After Definitive Radiotherapy for cT1a and cT1bN0M0 Esophageal Cancer - Kawamoto, Terufumi; Shikama, Naoto; Mine, Shinji; Sasai, Keisuke (Frontiers in Oncology, 2022)
Background Definitive radiotherapy (RT) for stage I esophageal cancer was reported to result in noninferior overall survival (OS) compared with surgery. However, only a few detailed reports of recurrence patterns and subsequent salvage treatments have been published. This study aimed to compare recurrence patterns and subsequent salvage treatments after definitive RT or chemoradiotherapy (CRT) between cT1a and cT1bN0M0 esophageal cancer (EC). Methods Patients with cT1a or cT1bN0M0 esophageal squamous cell carcinoma who received definitive RT or CRT were included. Survival outcomes, recurrence patterns, and salvage treatments were evaluated. Results In total, 40 patients with EC receiving RT or CRT were divided into two groups for evaluation: cT1a (20 patients) and cT1b (20 patients) groups. The 3-year OS rates were 83% and 65% (p = 0.06) and the 3-year progression-free survival rates were 68% and 44% (p = 0.15) in the cT1a and cT1b groups, respectively. Among those in the cT1a group, six had local recurrence and two had metachronous recurrence. Seven patients underwent salvage endoscopic submucosal dissection and one patient received argon plasma coagulation treatment. Among those in the cT1b group, six had local recurrence, one had regional recurrence, and one had both. Of these, one underwent salvage endoscopic submucosal dissection, one received photodynamic therapy, three underwent surgery, one received RT, and two received the best supportive care. Compared with the cT1b group, the cT1a group had a higher proportion of patients who underwent endoscopic treatments (p = 0.007). After the endoscopic treatments, no recurrences were observed in both groups. Conclusions Regional recurrence and distant metastasis were not observed in the cT1a group. A higher proportion of patients in the cT1a group received salvage endoscopic treatments, and their OS tended to be favorable.